2008
DOI: 10.1021/la801261h
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization of Functionalized Imidazolium-Based Ionic Liquids

Abstract: The surface composition of oligo(ethylene glycol) ether functionalized bis(trifluoromethylsulfonyl)imide ionic liquids has been studied by means of X-ray photoelectron spectroscopy (XPS). For [Me(EG)MIM][Tf 2N], [Et(EG) 2MIM][Tf 2N], and [Me(EG) 3MIM][Tf 2N], which vary by the number of ethylene glycol (EG) units (from 1 to 3), we have shown that the stoichiometry of the surface near region is in excellent agreement with the bulk stoichiometry, which confirms the high purity of the ionic liquid samples investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
155
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(170 citation statements)
references
References 34 publications
14
155
1
Order By: Relevance
“…For IL4, only minor changes with emission angle are seen (Figure S2), indicating the absence of major enrichment/orientation effects at the outer surface. This is in line with our earlier47 observations for other PEG ILs. For the signals of the [Tf 2 N] − anion, we find a minor surface enrichment of the CF 3 groups and a depletion of the corresponding SO 2 groups 21,22,47,52…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…For IL4, only minor changes with emission angle are seen (Figure S2), indicating the absence of major enrichment/orientation effects at the outer surface. This is in line with our earlier47 observations for other PEG ILs. For the signals of the [Tf 2 N] − anion, we find a minor surface enrichment of the CF 3 groups and a depletion of the corresponding SO 2 groups 21,22,47,52…”
Section: Resultssupporting
confidence: 94%
“…This analysis, along with the charge on atoms calculations, will allow for a comparison of the electronic structure of these methoxy and polyethylene‐glycol (PEG) ILs. Notably, for none of the ILs Si 2p signals, indicative of surface‐active polysiloxane contaminations,47,48 are observed in the presented data, confirming the high purity of our ILs.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Indeed, both experimental and theoretical investigations have recently found that the IL surface composition may be more or less populated with alkyl and/or fluorinated moieties depending on the type of anion and cation substituents. [27][28][29][30][31][32][33][34][35] However, the experimental conditions (distance between the metal target and liquid surface, gas pressure, current and time, and voltage change) used thus far have varied from one study to another, making it almost impossible to compare and correlate the influence of these parameters. 11,[22][23][24][25][26] Nonetheless, it is apparent that the size of NPs depends on the type of IL and on the discharge current.…”
Section: Introductionmentioning
confidence: 99%
“…9 In plasma processing as well as in material characterisation, the ionic liquids are exposed to high energy photons and electrons that can have an impact on the chemical reactions taking place or in worst case can be the cause of degradation effects in the material. Especially in some analytical methods such as photoelectron spectroscopy, [10][11][12][13][14] infrared spectroscopy, 15 Raman spectroscopy 16 or Auger electron spectroscopy, the ILs are exposed to different kinds of radiation by photons or electrons. A commonly used analytical method for the surface characterisation of different ionic liquids is XPS where monochromated or non-monochromated X-ray radiation is used for excitation.…”
Section: Introductionmentioning
confidence: 99%